INTEGRATING VISUAL AND ORAL PEDAGOGIES: A NEUROSCIENCE-INFORMED APPROACH TO EARLY CHILDHOOD EDUCATION - Nodira Turgunboyeva; Omila Odilovna Yuldasheva (Bright Mind Publishing, 2025)
This research studies the synergistic impact of integrating advanced visual and oral pedagogical strategies within kindergarten settings, with a focus on enhancing cognitive and socio-emotional development Employing a mixedmethods research design, including neuroscientific observations, detailed case studies, and longitudinal assessments, this study explores the nuanced effects of these methodologies. Findings reveal significant correlations between the strategic implementation of combined visual and oral techniques and enhanced neural plasticity, cognitive flexibility, and socio-emotional resilience. This paper advocates for the adoption of neuroscience-informed pedagogical practices, emphasizing the critical role of early childhood education in laying the foundation for lifelong learning and well-being.
Keywords: Early childhood education, kindergarten, visual learning, oral communication, neuroscience, cognitive development, socio-emotional learning, neural plasticity, pedagogical innovation, longitudinal studies.